Engendering Performance in the Late Iron Age - Back Danielsson, lng-Marie (Current Swedish Archaeology, 1999)
This paper deals with humanoid figures on gold foils from the Late Iron Age in Scandinavia. Interpreted as figures wearing masks, an effort is made to show the complexity, importance and significance of masking practices. The single Bornholm figures from the 6th century are interpreted as shamans performing rituals. Further, it is proposed that a restriction of masked appearances and performances to certain people (shamans) and places in the long run created stricter and more rigid gender roles in everyday life. The later gold-foil couples are seen as signs of divine communication, cosmological movement and seasonality, making up a mythology that legitimised political domination —the sacred lineage of rulers pivoting around an apical, ancestral cross-sex pair.